On Reenactment: Concepts, Methodologies, Tools - Baldacci, Cristina; Franco, Susanne (Mimesis Journal Books, 2022)
This book brings together dance and visual arts scholars to investigate the key methodological and theoretical issues concerning reenactment. Along with becoming an effective and widespread contemporary artistic strategy, reenactment is taking shape as a new anti-positivist approach to the history of dance and art, undermining the notion of linear time and suggesting new temporal encounters between past, present, and future. As such, reenactment has contributed to a move towards different forms of historical thinking and understanding that embrace cultural studies - especially intertwining gender, postcolonial, and environmental issues - in the redefinition of knowledge, historical discourses, and memory. This approach also involves questioning canons and genealogies by destabilising authorship and challenging both institutional and direct forms of transmission. The structure of the book playfully recalls that of a theatrical performance, with both an overture and prelude, to provide space for a series of theoretical and practice-based insights - the solos - and conversations - the duets - by artists, critics, curators, and theorists who have dealt with reenactment. The main purpose of this book is to demonstrate how reenactment as a strategy of appropriation, circulation, translation, and transmission can contribute to understanding history both in its perpetual becoming and as a process of reinvention, renarration, and resignification from an interdisciplinary perspective.